Mesoproterozoic Molar Tooth Structure Related to Increased Marine Oxygenation. Issue 1 (13th January 2023) - Tang, Dongjie; Fang, Hao; Shi, Xiaoying; Liang, Liyuan; Zhou, Limin; Xie, Baozeng; Huang, Kangjun; Zhou, Xiqiang; Wu, Mengting; Riding, Robert
Abstract: Marine carbonate fabrics are intrinsically related to ocean chemistry, physical processes and biological activity. Molar tooth structure (MTS), a globally distributed structure in Proterozoic carbonate sediments, has been widely studied for more than a century; yet its connections with physical and biological processes remain unclear. Using multiple techniques, we studied ∼1.57 Ga MTS and identified a connection between its occurrence and increased marine oxygenation. In our samples, the matrix surrounding MTS is typically dominated by carbonate mud with early diagenetic dolomite crystals. High I/(Ca + Mg) ratios (up to 4.1 μmol/mol) and negative Ce anomalies (∼0.8) detected in the matrix are consistent with the oxidative removal of inhibitors such as Fe 2+ and Mn 2+ in the water‐column that permitted carbonate "whiting" mud precipitation stimulated by cyanobacterial photosynthesis. This cohesive but not rigid seafloor carbonate mud was a prerequisite for synsedimentary MTS crack formation. Systematically higher carbon isotope (δ 13 C) values in MTS microspars, relative to host sediment, support origination of the cracks by methane degassing in the organic‐rich carbonate mud. Low, but non‐zero, I/(Ca + Mg) values of the MTS microspar suggest that the precipitation of the microspar that filled the MTS cracks was triggered by oxidative removal of residual Fe 2+ and Mn 2+ in porewater through mixing with overlying oxygenated seawater. We therefore propose that MTS formed under moderately oxygenated conditions and that its sporadic occurrence prior to ∼1.2 Ga reflects episodes of pulsed marine oxygenation in an overall anoxic setting. Plain Language Summary: Molar tooth structure (MTS) has been identified in Precambrian carbonate sedimentary rocks for more than a century. However, its formation and significance are still not fully understood. Precambrian ocean chemistry and low oxygen levels have previously been linked to MTS formation. Here, we use carbonate iodine data as a proxy for oxygenation, and carbon isotope data to decipher microbial processes. The iodine data indicate an oxygenated environment, and the carbon isotope data support previous suggestions that degassing of microbial methane was responsible for MTS crack formation. For the first time, we show that MTS occurred in oxygenated conditions. We propose that the oxidative removal of ions such as Fe 2+ and Mn 2+ that can inhibit carbonate precipitation was a key factor in the formation of the cohesive carbonate mud matrix of MTS, and in the rapid precipitation of the microspar cement that filled and preserved the MTS cracks. The relatively rare occurrence of MTS prior to 1, 200 Ma could therefore be a sedimentary indicator of sporadic marine oxygenation when marine conditions were mostly anoxic. Key Points: Petrographic and geochemical data constrain molar tooth structure (MTS) development in ∼1.57 Ga carbonates from North China Microbially induced water column carbonate mud and CH4 degassing from the sediment are critical for MTS formation The connection between MTS formation and marine oxygenation suggests MTS as a sedimentary redox proxy